Low-glycaemic index diet to improve glycaemic control and cardiovascular disease in type 2 diabetes: design and methods for a randomised, controlled, clinical trial. Issue 7 (7th July 2016) - Chiavaroli, Laura; Mirrahimi, Arash; Ireland, Christopher; Mitchell, Sandra; Sahye-Pudaruth, Sandhya; Coveney, Judy; Olowoyeye, Omodele; Maraj, Tishan; Patel, Darshna; de Souza, Russell J; Augustin, Livia S A; Bashyam, Balachandran; et al.
Abstract : Introduction: Type 2 diabetes (T2DM) produces macrovascular and microvascular damage, significantly increasing the risk of cardiovascular disease (CVD), renal failure and blindness. As rates of T2DM rise, the need for effective dietary and other lifestyle changes to improve diabetes management become more urgent. Low-glycaemic index (GI) diets may improve glycaemic control in diabetes in the short term; however, there is a lack of evidence on the long-term adherence to low-GI diets, as well as on the association with surrogate markers of CVD beyond traditional risk factors. Recently, advances have been made in measures of subclinical arterial disease through the use of MRI, which, along with standard measures from carotid ultrasound (CUS) scanning, have been associated with CVD events. We therefore designed a randomised, controlled, clinical trial to assess whether low-GI dietary advice can significantly improve surrogate markers of CVD and long-term glycaemic control in T2DM. Methods and analysis: 169 otherwise healthy individuals with T2DM were recruited to receive intensive counselling on a low-GI or high-cereal fibre diet for 3 years. To assess macrovascular disease, MRI and CUS are used, and to assess microvascular disease, retinal photography and 24-hour urinary collections are taken at baseline and years 1 and 3. Risk factors for CVD are assessed every 3 months. Ethics and dissemination: The study protocol and consent form have been approved by the research ethics board of St. Michael's Hospital. If the study shows a benefit, these data will support the use of low-GI and/or high-fibre foods in the management of T2DM and its complications. Trial Registration number: NCT01063374; Pre-results.